RELATIONSHIP BETWEEN THE LEVEL OF CIGARETTE SMOKE EXPOSURE AND SERUM TRIGLYCERIDE LEVELS AMONG STUDENTS - Muhammad Sony Al-Jufri; Yulia Ratna Dewi; Yulita Maulani (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Cigarette smoke exposure is a significant health threat that may trigger lipid metabolism disorders, particularly by increasing serum triglyceride levels through nicotine-stimulated production of Very Low-Density Lipoprotein (VLDL). This study aimed to analyze the correlation between cigarette smoke exposure levels and serum triglyceride levels in students to identify cardiovascular risks among the productive age group. This study employed an analytical observational design with a cross-sectional approach. A total of 83 participants were selected using a purposive sampling technique. Participants' levels of exposure to cigarette smoke were assessed, and their serum triglyceride levels were analyzed using the GPO-PAP enzymatic method. Statistical analysis was performed to determine the significance of the association between smoke exposure levels and serum triglyceride levels. The findings indicate no statistically significant correlation between the level of cigarette smoke exposure and serum triglyceride levels among the study participants (Spearman's rho, p = 0.882). Most participants were classified as having mild cigarette smoke exposure and exhibited serum triglyceride levels within the normal reference range. Furthermore, the relatively homogeneous exposure levels and the young age of the participants may have contributed to the limited variability observed in the study. In conclusion, mild cigarette smoke exposure was not significantly associated with serum triglyceride levels among young adults.